Comparison of a Small Central versus a Large Peripheral Perforator in a Rat Model of Extended Dorsal Three–Vascular Territory Perforator Flap. Issue 2 (February 2017) - Ding, Jian; Feng, Xiaoliang; Gao, Weiyang; Yan, Hede; Tao, Xianyao; Wang, Long; Tang, Maolin
Abstract : Background: Selection of suitable perforators is critical for satisfactory postreconstructive surgery outcome. This study aims to compare a small central versus a large peripheral perforator flap in a rat extended dorsal three–vascular territory perforator flap model. Methods: An extended intercostal artery perforator flap with three vascular territories was used to model a small central perforator flap. An extended deep circumflex iliac artery flap with three vascular territories was used to model a large peripheral perforator flap. Flap viability, angiography, and perfusion were compared. Results: Intercostal artery flaps showed significantly higher relative viable area than deep circumflex iliac artery flaps (98.5 ± 3.2 percent versus 87.1 ± 7.3 percent; p < 0.01). Angiography revealed that the anatomical and the first adjacent territories were perfused successfully in both types of flap, but the second adjacent territory of deep circumflex iliac artery flaps was not perfused sufficiently, thus ultimately leading to flap necrosis. Perfusion at the anatomical and the first adjacent territories of both types of flap increased significantly for 3 days ( p < 0.05) and became stable 5 to 7 days after surgery. Perfusion at the second adjacent territory of deep circumflex iliac artery flaps diminished continuously. Conclusions: A small central perforator may supply a larger vascular territory than a large peripheral perforator. Both the size and the location of a perforator should be considered for optimizing the design of an extended perforator flap. Abstract : Supplemental Digital Content is available in the text.